2021
DOI: 10.1155/2021/6657673
|View full text |Cite
|
Sign up to set email alerts
|

Hirudo Lyophilized Powder Ameliorates Renal Injury in Diabetic Rats by Suppressing Oxidative Stress and Inflammation

Abstract: As diabetic nephropathy (DN) is one of the most common and destructive microvascular complications of diabetes mellitus, the goal of this study, therefore, was to investigate the renal protective effect and latent mechanisms of Hirudo lyophilized powder on diabetic rats. In this study, all rats were randomly assigned into the control group and diabetic group. The rats of diabetic group were injected with low-dose STZ (35 mg/kg) intraperitoneal plus high-fat diet to induce diabetes. Then, the successful diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…It should be noted that in the experimental groups, an increase in body weight and length was observed in both newborns and 15-day-old rats in comparison with the control groups Table 3 (p <0.05). An increase in body weight in early post-embryonic ontogeny after the hirudological influence was observed in our previous works and the results of other authors (Aminov et al, 2022;Davoodi et al, 2021;Amani et al, 2021;Yang et al, 2021;Trenholme et al , 2021) as a morphogenetic effect of the substances of medicinal leeches. During the external examination, no developmental abnormalities were noted in either of the groups.…”
Section: Control Experimentalsupporting
confidence: 81%
See 2 more Smart Citations
“…It should be noted that in the experimental groups, an increase in body weight and length was observed in both newborns and 15-day-old rats in comparison with the control groups Table 3 (p <0.05). An increase in body weight in early post-embryonic ontogeny after the hirudological influence was observed in our previous works and the results of other authors (Aminov et al, 2022;Davoodi et al, 2021;Amani et al, 2021;Yang et al, 2021;Trenholme et al , 2021) as a morphogenetic effect of the substances of medicinal leeches. During the external examination, no developmental abnormalities were noted in either of the groups.…”
Section: Control Experimentalsupporting
confidence: 81%
“…Nowadays preference is given to natural substances that have virtually no side effects or contraindications. These include substances obtained from medicinal leeches that have a wide range of therapeutic effects (Aminov et al, 2022;Davoodi et al, 2021;Amani et al, 2021;Yang et al, 2021;Aminov et al, 2021). These substances have shown effectiveness in the prevention and treatment of a significant number of diseases in animals and humans (Fattakhov et al, 2021;Trenholme et al, 2021;Amani et al, 2021;Afroz et al, 2020;Akalın et al, 2020;Curcio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A NMA [ 90 ] examining proprietary Chinese medicines derived from leeches for atherosclerosis treatment revealed that these medicines, whether used with or without statins, demonstrated superior efficacy in reducing intima-media thickness and decreasing plaque area and count in comparison to oral statins alone. Of particular significance, both Dilong and leeches exhibit lipid-lowering, antithrombotic, anticoagulant, and anti-inflammatory effects [ 91 – 94 ]. These combined effects could potentially contribute to achieving the highest overall efficacy rate of Shuxuetong injection in TIA treatment while effectively reducing the likelihood of cerebral infarction progression.…”
Section: Discussionmentioning
confidence: 99%
“…LTF, which consists of Radix Rhei Et Rhizome, Persicae Semen, Panax notoginseng (Burk.) F. H. Chen Ex C. Chow, and Hirudo has been used to treat diabetic secondary symptoms, such as DR, diabetic nephropathy, diabetic encephalopathy, and diabetic cardiomyopathy [16][17][18][19]. Previous studies from our lab have shown that LTF ameliorates DR via certain mechanisms, involving the miR-200b and the p38 MAPK/NF-κB pathway [13,14].…”
Section: Discussionmentioning
confidence: 99%